Designing a place called home : reordering the suburbs - Wentling, James W. (Springer, 2017)
"This insightful volume shares design ideas to help builders, planners and architects create mass-produced affordable housing that pushes suburban development in more sustainable, liveable directions. The author argues that improving the quality of design in our new homes and communities for greater resiliency, sustainability, and equality, we can build neighborhoods and communities where residents feel more connected t their homes and to one another. Through text, photographs and illustrations, the book reviews prototypical American housing design, then suggest ways to both learn from the past as well as adapt for new environmental imperatives, demographic changes and lifestyle needs. Written by a practicing architect with 25+ years of experience optimizing residential design, this pioneering approach to suburban building will inspire readers to view mass produced housing through a new, modern lens."--